Non Financial Disclosure and Financial Performance in UAE Industrial Companies - Ali Fadhil Jaber; Auday Safa-Aldeen Fadhil (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Integrated reporting combines financial and non-financial information to provide a comprehensive view of corporate performance. Specific Background: UAE industrial companies have increasingly adopted integrated reporting practices to improve disclosure quality. Knowledge Gap: Limited evidence exists regarding the relationship between non-financial disclosure and financial performance in UAE industrial companies. Aims: This study examines the relationship between non-financial disclosure in integrated reports and financial performance measured by earnings per share (EPS) and current liquidity during 2016–2024. Results: The findings reveal a positive and statistically significant relationship between non-financial disclosure and both EPS and current liquidity. ARDL analysis indicates a significant long-run positive relationship with current liquidity, while the long-run relationship with EPS is not statistically significant. Novelty: The study applies International Integrated Reporting Council disclosure dimensions and ARDL estimation to UAE industrial companies over an extended period. Implications: The findings support greater emphasis on non-financial disclosure and the monitoring of integrated reporting practices to provide more comprehensive information for stakeholders and financial decision-making. Highlights: • Non-financial reporting practices showed a positive association with earnings per share among UAE industrial companies.• Integrated report disclosures were positively linked to current liquidity in both short-term and long-term analyses.• Disclosure levels increased substantially following the adoption of integrated reporting practices within the sampled firms. Keywords: Integrated Reporting, Non Financial Disclosure, Financial Performance, Earnings Per Share, Current Liquidity